Climate warming could increase recruitment success in glacier foreland plants - Mondoni, Andrea (Ann Bot, 2015)
Background and Aims Glacier foreland plants are highly threatened by global warming. Regeneration from seeds on deglaciated terrain will be crucial for successful migration and survival of these species, and hence a better understanding of the impacts of climate change on seedling recruitment is urgently needed to predict future plant persistence in these environments. This study presents the first field evidence of the impact of climate change on recruitment success of glacier foreland plants. Methods Seeds of eight foreland species were sown on a foreland site at 2500 m a.s.l., and at a site 400 m lower in altitude to simulate a 2·7 °C increase in mean annual temperature. Soil from the site of origin was used to reproduce the natural germination substrate. Recruitment success, temperature and water potential were monitored for 2 years. The response of seed germination to warming was further investigated in the laboratory. Key Results At the glacier foreland site, seedling emergence was low (0 to approx. 40 %) and occurred in summer in all species after seeds had experienced autumn and winter seasons. However, at the warmer site there was a shift from summer to autumn emergence in two species and a significant increase of summer emergence (13–35 % higher) in all species except two. Survival and establishment was possible for 60–75 % of autumn-emerged seedlings and was generally greater under warmer conditions. Early snowmelt in spring caused the main ecological factors enhancing the recruitment success. Conclusions The results suggest that warming will influence the recruitment of glacier foreland species primarily via the extension of the snow-free period in spring, which increases seedling establishment and results in a greater resistance to summer drought and winter extremes. The changes in recruitment success observed here imply that range shifts or changes in abundance are possible in a future warmer climate, but overall success may be dependent on interactions with shifts in other components of the plant community.